Going concern modifications and related disclosures in the Italian stock market: do regulatory improvements help investors in capturing financial distress? - Brunelli, Sandro; Carlino, Chiara; Castellano, Rosella; Giosi, Alessandro (Journal of management and governance, 2021)
This paper investigates the investor reaction to audit reports containing a going concern modification (GCM) in the Italian market following new amendments regarding auditing regulations and public financial information disclosures. We applied the event study (ES) methodology to short event windows considering Italian listed companies during the period 2009–2015. Our findings partially contradict previous studies revealing a systematic negative impact of GCMs, especially when a GCM is attached to unqualified opinions. We clearly observe that Italian auditors have a strong higher propensity to issue a GCM than to express a qualification. Moreover, we find other interesting results that contradict the mainstream literature, detecting a stronger negative reaction in the case of recurring GCMs and when the modification is issued by non-Big 4 auditing firms. These differences could be explained considering the environmental characteristics of the Italian market such as the ownership structure, governance mechanisms and accounting culture, where minority investors act against ownership in accordance with the type II agency problem. Our empirical results suggest that the domestic and international regulatory amendments during the study period have increased the value relevance of GCMs and the usefulness of financial disclosures. This study might be of interest to practitioners and regulators in regard to contributing to the introduction of further regulatory interventions that will enhance both the informativeness of audit reports and awareness of investors in regard to going concern uncertainty.